Matching the impositions of the farming and research systems as a prelude to farming systems research - Kaufmann, Ralph R. von (International Livestock Centre for Africa, 1986)
Deals with the implications of the constraints imposed on achievement of research goals by the impositions of the research and farming systems as they interact in a research programme drawing examples from the experience of the ILCA Subhumid Zone Programme presents the estimated net present value of ILCA's investment as well as the anticipated financial returns to fodder banks in the same programme.